Peningkatan Motivasi Dan Hasil Belajar PAI Dan BP Materi Bersikap Dan Berperilaku Jujur Menggunakan Aplikasi Voice Note Whatsapp: Pada Siswa Kelas V SDN 173105 Tarutung Semester 1 Tahun Pelajaran 2021/2022 - Gultom, Poltak (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2022)
Classroom action research is motivated by the low learning outcomes of PAI and BP on the material of honest attitude and behavior that has not yet reached the KKM. Attempts to solve the problem using the WhatsApp Voice note application. The type of research is classroom action research. The research subjects were 17 students. The data collection technique used observation, test and documentation techniques. Validation of data using triangulation technique. The data analysis method used qualitative data analysis. The results showed an increase in student motivation from 9 students (52.94%), increased to 12 students (70.59%), and in the second cycle there were 16 students (94.12%), student learning outcomes data from 4 students (23 ,53%), increased to 9 students (52,94%), and in the second cycle there were 15 students (88,24%). The average learning outcomes also increased by 63.53 to 74.12 and 84.71. Based on the explanation above, it can be concluded that the use of the WhatsApp Voice note application can increase the motivation and learning outcomes of the fifth grade students of SDN 173105 Tarutung Semester 1 of the 2021/2022 Academic Year.